Tradisi Pasatowan Masyarakat Suku Jawa Ditinjau dari Akidah Islam Desa Sidoharjo I Pasar Miring Kecamatan Pagar Merbau Kabupaten Deli Serdang - Syaharani, Kurnia (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
Pasatowan is a tradition of the Javanese people which is carried out by counting the weton of someone who will hold a wedding as a material for consideration of suitability between men and women, Sidoharjo Village I, the tilted market, where the majority of the Javanese population also carries out the Pasatowan tradition, only at this time this tradition has been rare. That's why the author wants to reveal the problem of pasatowan in the village of Sidoharjo I slanted market which aims to find out how the pasatowan tradition of the Javanese people of Sidoharjo I slanted market is, what is the view of the people of Sidoharjo I slanted market. The research method used is field research (field research) with a qualitative approach, the data sources used are primary data sources and secondary data sources, as well as using data collection techniques in the form of interviews after which the data is analyzed. The results of the study show that the pasatowan tradition is still carried out by the Javanese people in the village of Sidoharjo I, the tilted market, according to Islam, the pasatowan tradition is an urf which can occur in two possibilities because in Islam there are urf authentic and urf fasid.